Vγ9Vδ2 T Cells Concurrently Kill Cancer Cells and Cross-Present Tumor Antigens - Holmen Olofsson, Gitte; Idorn, Manja; Carnaz Simões, Ana Micaela; Aehnlich, Pia; Skadborg, Signe Koggersbøl; Noessner, Elfriede; Debets, Reno; Moser, Bernhard; Met, Özcan; thor Straten, Per (Frontiers in Immunology, 2021)
The human Vγ9Vδ2 T cell is a unique cell type that holds great potential in immunotherapy of cancer. In particular, the therapeutic potential of this cell type in adoptive cell therapy (ACT) has gained interest. In this regard optimization of in vitro expansion methods and functional characterization is needed. We show that Vγ9Vδ2 T cells, expanded in vitro with zoledronic acid (Zometa or ZOL) and Interleukin-2 (IL-2), capacity to kill cancer cell targets increased over time. Thus, Vγ9Vδ2 T cells expanded for 25 days in vitro killed cancer cells more efficiently than Vγ9Vδ2 T cells expanded for 9 days. These data are supported by phenotype characteristics, showing increased expression of CD56 and NKG2D over time, reaching above 90% positive cells after 25 days of expansion. At the early stage of expansion, we demonstrate that Vγ9Vδ2 T cells are capable of cross presenting tumor antigens. In this regard, our data show that Vγ9Vδ2 T cells can take up tumor-associated antigens (TAA) gp100, MART-1 and MAGE-A3 - either as long peptide or recombinant protein – and then present TAA-derived peptides on the cell surface in the context of HLA class I molecules, demonstrated by their recognition as targets by peptide-specific CD8 T cells. Importantly, we show that cross presentation is impaired by the proteasome inhibitor lactacystin. In conclusion, our data indicate that Vγ9Vδ2 T cells are broadly tumor-specific killers with the additional ability to cross-present MHC class I-restricted peptides, thereby inducing or supporting tumor-specific TCRαβ CD8 T cell responses. The dual functionality is dynamic over time during in vitro expansion, yet, both functions are of interest to explore in ACT for cancer therapy.